Neuromuscular recruitment characteristics of quadriceps femoris muscles during Wingate anaerobic test - Okano, A. H.; Moraes, A. C.; Bankoff, A. D. P.; Gassi, E. R.; Okano, R. O.; Cyrino, E. S. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The aim of the present study is to investigate the neuromuscular recruitment characteristics of Vastus Lateralis (VL), Vastus Medialis (VM), and RF during WAnT. The results show that the differences in morphology, architecture, and biomechanics of these muscles induced in specific motor strategy of RF and could be reflected in a different motor unit activity, which may have produced different signal characteristics of EMG-RMS during WAnT.